Hack I.T. : security through penetration testing - Klevinsky, T. J. (Addison-Wesley, 2002)
"This book covers not just the glamorous aspects such as the intrusion act itself, but all of the pitfalls, contracts, clauses, and other gotchas that can occur. The authors have taken their years of trial and error, as well as experience, and documented a previously unknown black art." --From the Foreword by Simple Nomad, Senior Security Analyst, BindView RAZOR Team Penetration testing--in which professional, "white hat" hackers attempt to break through an organization's security defenses--has become a key defense weapon in today's information systems security arsenal. Through penetration testing, I.T. and security professionals can take action to prevent true "black hat" hackers from compromising systems and exploiting proprietary information. Hack I.T. introduces penetration testing and its vital role in an overall network security plan. You will learn about the roles and responsibilities of a penetration testing professional, the motivation and strategies of the underground hacking community, and potential system vulnerabilities, along with corresponding avenues of attack. Most importantly, the book provides a framework for performing penetration testing and offers step-by-step descriptions of each stage in the process. The latest information on the necessary hardware for performing penetration testing, as well as an extensive reference on the available security tools, is included. Comprehensive in scope Hack I.T. provides in one convenient resource the background, strategies, techniques, and tools you need to test and protect your system--before the real hackers attack. Specific topics covered in this book include: Hacking myths Potential drawbacks of penetration testing Announced versus unannounced testing Application-level holes and defenses Penetration through the Internet, including zone transfer, sniffing, and port scanning War dialing Enumerating NT systems to expose security holes Social engineering methods Unix-specific vulnerabilities, such as RPC and buffer overflow attacks The Windows NT Resource kit Port scanners and discovery tools Sniffers and password crackers Web testing tools Remote control tools Firewalls and intrusion detection systems Numerous DoS attacks and tools 0201719568B01042002.